INTERWELL CONNECTIVITY TESTS IN WATERFLOOD SYSTEMS - (:unkn) unknown (My University, 2009)
Well testing is a common and important tool of reservoir characterization. Many well testing methods have been developed in order to obtain different reservoir properties. Interference tests and pulse tests are used to quantify communication between wells. These methods are often applied to two or more wells with only one active well sending the signals (by changing flow rates) and the shut-in observation wells receiving them. However, for a large field such as a waterflood system, multiple wells are present and most of them are active at the same time. In this case, a pulse test or an interference test with only one active well is difficult to conduct since the signal can be distorted by other active wells in the reservoir.

Interwell connectivity represents the ability of fluid to flow from one well to the others. It is a function of distance and reservoir properties between wells. In waterfloods, information on interwell connectivity is essential in reservoir management, infill drilling and field development plan. This study presents a novel technique to quantify interwell connectivity in a waterflood system based on fluctuations of bottom-hole pressure of both injectors and producers. The interwell connectivity between active and observation wells were quantified by calculating interwell connectivity coefficients. An interwell connectivity coefficient is the fraction of pressure change at an observation well due to an active well of the total pressure change at the observation well due to all active wells. More details on the interwell connectivity coefficients are provided later in this report. Both active and observation wells could be active at the same time. The technique utilizes a constrained multivariate linear regression analysis to obtain information about permeability trends, channels and barriers. Analytical models for the multi-well systems with water injection are derived based on the concept of regional reservoir pressure trend and the pseudo-steady state pressure behavior. Solutions are provided for fully penetrating vertical wells, fully penetrating hydraulic fractures and horizontal wells. Different common reservoir characteristics were investigated including: homogeneous reservoirs, anisotropic reservoirs, reservoirs with high permeability channels, partially sealing barriers and sealing barriers and naturally fractured reservoirs which exhibited dual porosity behavior.

An analytical model, which is based on pseudo-steady state solutions of different wellbore conditions in a closed rectangular reservoir, has been developed for the new technique. By applying the analytical model, a new parameter, called the relative interwell permeability, is introduced to quantify the interwell connectivity: This parameter does not depend on the distance between wells and the wellbore conditions (vertical, horizontal or hydraulically fractured wellbores). A technique utilizing the least squares regression analysis is used to estimate the average pressure change at each test time interval. Thus, reservoir pore volume, total average porosity and reservoir compartmentalization can be inferred from the results. In this study, a new analytical model was also developed for a technique published by Albertoni and Lake (2003) that used production data of a waterflood to infer interwell connectivity. The results showed excellent agreement for a reservoir flowing under a steady state condition.

Instrumented oil fields, where down-hole pressure sensors are installed at every well to monitor real-time data, are becoming very common. Hence, collecting bottom hole pressure data at every well at any given time is no longer an impossible task. This study provides a robust technique to utilize these data for reservoir characterization. The results obtained from the technique are essential for field development plans, which aim to optimize oil production by changing and managing well patterns, well locations and infill drilling. The study also provides better understanding of the reservoir behaviors of a multi-well system in which both injectors and producers are present.

The main conclusions drawn from this study can be stated as follows:

1. The proposed technique using bottom hole pressure data is more robust than a similar technique that uses production data as it provides better results with less data points and without the need of subjective judgments. The interwell connectivity coefficients obtained can be used to identify reservoir anisotropy, high permeability channels and flow barriers. The validity of the results for different heterogeneous reservoirs containing different wells of different wellbore conditions such as fully penetrating vertical wells, fully penetrating hydraulic fractures and horizontal wells were verified using data from a commercial black oil simulator.

2. Pressure transient solutions of a well in a multiwell system are used to derive the mathematical model for the technique. Thus, this study introduced a new parameter called relative interwell permeability to quantify interwell connectivity. The relative interwell permeability does not depend on distance between wells or wellbore conditions.

3. The new procedure also allows the calculation of average pressure change for each test time interval. Using a material balance equation, the total pore volume can be calculated. Furthermore, based on these pressure results, reservoir compartments can be identified.

4. The test design is flexible. This study has shown that active wells could be either injectors or producers and observation wells could be injectors, producers or shut-in wells. This is important for the field applications as the actual field situations may vary from one reservoir to another.

5. Under the pseudo-steady state condition, pressure solution for a well in a naturally fractured reservoir, which behaves like a dual-porosity system, is the same as the solution for a well in a homogeneous reservoir given that the effective permeability for the naturally fractured reservoir is equal to the permeability of the homogeneous reservoir. Thus, the technique introduced in this study to determine interwell connectivity is applicable to both a naturally fractured reservoir and homogeneous reservoir.

6. Different wellbore conditions such as vertically fractured wells and horizontal wells were considered in this study. The interwell connectivity information can also be obtained from different types of wellbore conditions. With the analytical model, the systems with different wellbore conditions can be analyzed and the resulting relative interwell permeabilities can be used to infer the formation properties between active and observation wells.

7. The analytical approach can be used to develop an analytical model for production data from a waterflood system flowing under steady state condition. The results obtained from analytical models fit well with those obtained from synthetic models in the Albertoni and Lake study. Thus, the analytical solution gives a better understanding to the techniques available in the literature that require the use of production data.
Keywords: Fluid dynamics; Petroleum engineering; Oil field flooding; Oil wells--Testing